Effects of bowel preparation on the human gut microbiome and metabolome - Nagata, Naoyoshi; Tohya, Mari; Fukuda, Shinji; Suda, Wataru; Nishijima, Suguru; Takeuchi, Fumihiko; Ohsugi, Mitsuru; Tsujimoto, Tetsuro; Nakamura, Tomoka; Shimomura, Akira; Yanagisawa, Naohiro; Hisada, Yuya; et al. (Scientific reports, 2019)
Large bowel preparation may cause a substantial change in the gut microbiota and metabolites. Here, we included a bowel prep group and a no-procedure control group and evaluated the effects of bowel prep on the stability of the gut microbiome and metabolome as well as on recovery. Gut microbiota and metabolome compositions were analyzed by 16S rRNA sequencing and capillary electrophoresis time-of-flight mass spectrometry, respectively. Analysis of coefficients at the genus and species level and weighted UniFrac distance showed that, compared with controls, microbiota composition was significantly reduced immediately after the prep but not at 14 days after it. For the gut metabolome profiles, correlation coefficients between before and immediately after the prep were significantly lower than those between before and 14 days after prep and were not significantly different compared with those for between-subject differences. Thirty-two metabolites were significantly changed before and immediately after the prep, but these metabolites recovered within 14 days. In conclusion, bowel preparation has a profound effect on the gut microbiome and metabolome, but the overall composition recovers to baseline within 14 days. To properly conduct studies of the human gut microbiome and metabolome, fecal sampling should be avoided immediately after bowel prep.